Dinamika Interaksi Reseptor ACE2 dan SARS-CoV-2 Terhadap Manifestasi Klinis COVID-19 - Risma Ikawaty (KELUWIH: Jurnal Kesehatan dan Kedokteran, 2020)
Abstract— Background: A human severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is known to be responsible for coronavirus disease 2019 (COVID-19). Pulmonary complications has been considered as the classical clinical manifestations until symptoms on the extra-pulmonary organs may also occur recently, which might be linked to the presence of angiotensin-converting enzyme 2 (ACE2) receptor. Objective: This article evaluates clinical manifestation of COVID-19 and the presence of ACE2 receptor by looking at its interaction to SARS-CoV-2. Methods: 27 articles in English have been selected through search engine PubMed and Google Scholar by using specific keywords. These articles include research journals, case report, systematic review and meta-analysis, and textbooks. Result: Pathogenesis of COVID-19 begins with the binding of spike protein SARS-CoV-2 to ACE2 receptor of host cells. Clinical manifestation of COVID-19 is no longer limited to the pulmonary system but also extra-pulmonary systems since ACE2 receptor abundantly distributed on the other organs. Further, genetic variations of region binding protein of viral spike protein and ACE2 receptor may predispose clinical manifestation of COVID19. Conclusions: Dynamic interplay between SARS-CoV-2 and receptor ACE2 has great implication to the clinical symptoms. Genetic variation of spike protein SARS-CoV-2 play role not only for cross transmission but also its virulence, while genetic variation of human receptor ACE2 influences its susceptibility or resistance against the infection. Keywords: ACE2 receptor, Coronavirus Diseases-19, clinical manifestation, SARS-CoV-2, genetic variation. Abstrak— Virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) merupakan penyebab utama dari coronavirus disease 2019 (COVID-19). Komplikasi pernapasan diangap sebagai gejala klinis klasik hingga akhirnya timbul berbagai manifestasi klinis di organ lain sebagai gejala awal COVID19. Hal ini kemudian dihubungkan dengan reseptor angiotensin-converting enzyme 2 (ACE2). Artikel ini mengevaluasi manifestasi klinis yang disebabkan interaksi antara reseptor ACE2 dan SARS-CoV-2. PubMed dan Google Scholar digunakan untuk mencari artikel dengan kata kunci yang spesifik untuk COVID-19, SARS-CoV-2, reseptor ACE2, variasi genetik, dan manifestasi klinisnya. Dua puluh tujuh artikel berbahasa Inggris yang digunakan termasuk jurnal penelitian, laporan kasus, systematic review, meta-analysis, dan buku teks. Patogenesis COVID19 dimulai dengan ikatan protein Spike SARS-CoV-2 dan reseptor ACE2. Studi memperlihatkan bahwa reseptor ACE2 ditemui di berbagai jaringan/organ selain organ sistem respirasi sehingga memperlihatkan gejala klinis yang berbeda. Selain itu variasi genetik yang terdapat pada protein spike dari virus dan reseptor ACE2 juga merupakan faktor penting pada terjadinya COVID19. Penulis menyimpulkanbahwa dinamika interaksi antara reseptor ACE2 dan protein spike SARS-CoV-2 termasuk variasi genetic, keduanya memegang peranan penting terhadap suseptibilitas/resistensi dan manifestasi klinis COVID19. Kata kunci: Coronavirus Diseases-19, manifestasi klinis, reseptor ACE2, SARS-CoV-2, variasi genetik.